The Geographic Information System of The Distribution of Larva Free Rates in Kediri City Area - Ashafidz Fauzan Dianta; Toga Aldila Cinderatama; Fery Sofian Efendi (Politeknik Negeri Batam, 2021)
The process of representing the distribution of larva free numbers in the district of Kediri which is not visible makes the monitoring process for larva free rates per region less effective and efficient. Therefore, a geographic information system is needed to describe the distribution of larva free numbers in the Kediri Regency area. The design and development of this information system is carried out using two methods, one of which is the data collection method by conducting interviews with one of the staff in the Kediri district Health Office, observing and looking for references related to research.The existence of a Geographical Information System for the Distribution of Larva Free Numbers, helps the Kediri District Health Office in terms of recapitulating data and monitoring the risk of the distribution of larva numbers in the Kediri Regency area. The Geographical Information System for the Distribution of Larva Free Numbers in Kediri Regency was successfully designed and built and can display the distribution of larva free numbers in the form of markers on a map. The Geographical Information System for the Distribution of Larva Free Numbers in Kediri Regency uses PHP, HTML, CSS, JavaScript, MySQL, and the laravel framework.